The therapeutic implications of the genomic analysis of malignant pleural mesothelioma - Zauderer, Marjorie G. (Nat Commun, 2021)
Delineation of the genomic complexities of malignant pleural mesothelioma (MPM) has lagged behind other malignancies. Zhang et al. meaningfully add to our understanding of MPM, and their findings emphasize the need to combine drug development efforts with appropriate predictive biomarkers.